2015
DOI: 10.5194/gmd-8-221-2015
|View full text |Cite
|
Sign up to set email alerts
|

A high-order conservative collocation scheme and its application to global shallow-water equations

Abstract: Abstract. In this paper, an efficient and conservative collocation method is proposed and used to develop a global shallow-water model. Being a nodal type high-order scheme, the present method solves the pointwise values of dependent variables as the unknowns within each control volume. The solution points are arranged as Gauss-Legendre points to achieve high-order accuracy. The time evolution equations to update the unknowns are derived under the flux reconstruction (FR) framework (Huynh, 2007). Constraint co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…14 Recall that the diagonal element of any operator P are equal to the spacing between flux points. 15 This dependence on the mesh size in the normal direction to the face is similar to that of the interior penalty approach used in finite element methods. thermal condition, is proven to be bounded by physical data provided by the user.…”
Section: Entropy Stability Analysis For the Solid Wall Boundary Condi...mentioning
confidence: 71%
See 2 more Smart Citations
“…14 Recall that the diagonal element of any operator P are equal to the spacing between flux points. 15 This dependence on the mesh size in the normal direction to the face is similar to that of the interior penalty approach used in finite element methods. thermal condition, is proven to be bounded by physical data provided by the user.…”
Section: Entropy Stability Analysis For the Solid Wall Boundary Condi...mentioning
confidence: 71%
“…This factor is also important because it allows to achieve the correct asymptotic order of accuracy and yields an increase in the strength of M with increased resolution. 15 Summarizing Equation ( 54), the penalty at the face point is the sum of three terms:…”
Section: Entropy Stability Analysis For the Solid Wall Boundary Condi...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the DFR method results in a scheme equivalent to the weak form of the nodal discontinuous Galerkin method in one dimension and on multidimensional elements with tensor product bases [1,3]. It should be noted that these ideas are not entirely new in geophysical applications since the 3rd order scheme presented in [31] may also be considered as a special case of the DFR method. In § 4.1, an overview of the basic properties of the method in one dimension is presented and its extensions to two dimensions and curved geometry is discussed in § 4.2.…”
Section: Spatial Discretizationmentioning
confidence: 99%